Preparation and characterization of polyhydroxybutyrate/polycaprolactone nanocomposites - Liau, Cha Ping; Ahmad @ Ayob, Mansor; Shameli, Kamyar; Wan Yunus, Wan Md. Zin; Ibrahim, Nor Azowa; Zainuddin, Norhazlin; Then, Yoon Yee (Hindawi Publishing Corporation, 2014)
Polyhydroxybutyrate (PHB)/polycaprolactone (PCL)/stearate Mg-Al layered double hydroxide (LDH) nanocomposites were prepared via solution casting intercalation method. Coprecipitation method was used to prepare the anionic clay Mg-Al LDH from nitrate salt solution. Modification of nitrate anions by stearate anions between the LDH layers via ion exchange reaction. FTIR spectra showed the presence of carboxylic acid (COOH) group which indicates that stearate anions were successfully intercalated into the Mg-Al LDH. The formation of nanocomposites only involves physical interaction as there are no new functional groups or new bonding formed. X-ray diffraction (XRD) and transmission electron microscopy (TEM) indicated that the mixtures of nanocomposites are intercalated and exfoliated types. XRD results showed increasing of basal spacing from 8.66 to 32.97 Å in modified stearate Mg-Al LDH, and TEM results revealed that the stearate Mg-Al LDH layers are homogeneously distributed in the PHB/PCL polymer blends matrix. Enhancement in 300% elongation at break and 66% tensile strength in the presence of 1.0 wt % of the stearate Mg-Al LDH as compare with PHB/PCL blends. Scanning electron microscopy (SEM) proved that clay improves compatibility between polymer matrix and the best ratio 80PHB/20PCL/1stearate Mg-Al LDH surface is well dispersed and stretched before it breaks.